Decreasing of COD, Phosphate (PO4) and Detergent (LAS) Using Fixed Bedreactor with an Anaerobic Process - Munawar Ali (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2021)
In the absence of adequate management, the majority of laundry wastes, such as detergent and clothes softener, are typically dumped directly and unceremoniously into the channel that leads to a body of water. A Fixed Bed Reactor containing media in an anaerobic Bioball is one method that can be utilized to process laundry waste. Other methods include the underlying qualities of waste clothing is COD: Detergents: 291 mg/l Total: 29.74 mg N/l total P: 172.58 mg/l 29.12 mg/l. This study used a variety of COD concentrations to waste the early (So) = 280 mg/l, 232.8 mg/l (80% * So), 174.6 mg/l (60%) and 116 mg/l (40%) and discharge 150, 130, 110, 80, and 60 ml/minute, respectively. The best COD concentrations were found to be 91.06 percent for COD at the COD variation of 58.2 mg/l and 60 ml/min discharge, and the concentrations of phosphate (PO4) were found to be 82.13 percent at 20 percent waste discharge 60 mg/minute Concentrations of detergent and 76.13 percent at 20 percent waste discharge 60 mg/min Concentrations of phosphate According to the 2002 decision of the Governor of East Java Number 45, the concentration of bioball media meets the standard quality of raw liquid waste at concentrations of COD, phosphate (PO4), and detergents that are processed on a fixed bed reactor.